Psychological factors associated with successful outcomes in home haemodialysis. Issue 7 (18th June 2013) - Nearhos, Jane; Van Eps, Carolyn; Connor, Jason
Abstract: Aim: Performing haemodialysis therapy at home has been associated with improved survival for end‐stage kidney disease patients and can generally be delivered at a lower cost to the healthcare system when compared with centre and satellite unit dialysis. However, only a minority of dialysis dependent end‐stage kidney disease patients successfully sustain haemodialysis at home. Current practice for determining dialysis treatment modality and location takes into account medical suitability and social situation, but infrequently formally examines the contribution of psychological factors. This study explores demographic, health, and psychological factors that may predict patients' ability to sustain home haemodialysis. Methods: One hundred and thirteen successful and unsuccessful home haemodialysis users were recruited to the study, and 55 responded to self‐report measures. Demographic (age, gender, education level, carer support), health (comorbidities, diabetes, psychiatric condition) and psychological (locus of control beliefs, coping styles) information was used as predictor variables for the participants' time maintaining home therapy (Home Time). Results: In a three‐step regression, the model explained 32% of variance in Home Time. Coping styles significantly contributed 16% of the variance in Home Time after accounting for other variables. Adaptive Coping was significantly correlated with the length of time sustaining home therapy. Conclusion: Adaptive coping strategies are associated with improved ability to sustain home haemodialysis therapy. Evidence‐based psychological approaches can help patients develop more adaptive coping strategies. More research is needed to assess whether instituting these psychological interventions will assist patients to adopt and sustain dialysis therapies which require increased patient self‐management. Summary at a Glance: This study identifies that adaptive coping strategies can improve the success of maintaining home haemodialysis. Psychological interventions to help sustain successful home haemodialysis need further study.